Sensing technology for assessing motor behavior in ballet: A systematic review - Quadrado, V.; Moreira, M.; Ferreira, H.; Passos, P. (Sports Medicine - Open, 2022)
Background Human performance in classical ballet is a research field of growing interest in the past decades. Technology used to acquire data in human movement sciences has evolved, and is specifically being applied to evaluate ballet movements to better understand dancers` profiles. We aimed to systematically review sensing technologies that were used to extract data from dancers, in order to improve knowledge regarding the performance of ballet movements through quantification.